Taxonomic account of misidentified Saurida lessepsianus Russell, Golani and Tikochinski, 2015 from the east coast of India (Bay of Bengal) - Silpa S.; Shahana S.; Shashi Bhushan; A. Pavan Kumar; A. Mahapatra; A.K. Jaiswar (Journal of Indian Fisheries Association, 2023)
The objective of the current study was to tackle the problem of incorrect identification regarding Saurida lessepsianus. In prior research conducted along the eastern coast of India, it had been mistakenly labeled as Saurida undosquamis due to their similar physical characteristics. Through a comprehensive analysis involving both morphological and genetic data, this study serves to establish that the species referred to as S. undosquamis, identifiable by its upper caudal fin with distinctive black spots, along the eastern coastline of India (Bay of Bengal), is in fact S. lessepsianus. The misidentification arose from the assumption that the presence of black dots on the upper lobes of the caudal fin was a unique feature of S. undosquamis, which was later found that this trait is shared among certain species within the same genus. This underscores the necessity for applying the accurate scientific nomenclature to species, as precision in taxonomy is fundamental for effective conservation and management efforts. Consequently, this study significantly expands the documented range of S. lessepsianus to encompass the east coast of India (Bay of Bengal), in addition to its previously recognized habitats in the Mediterranean/Red Sea region and the eastern Arabian Sea.